An ontology for network services - Neves, José (2006)
Most of the network service specifications are implemented using relational databases or XML schemas. However, those specifications are not flexible and expressive enough to be extended with new service classes, different corporate policies, network configurations and deployment strategies; thus, most of the QoS management operations are implemented as hard-coded software components. This paper presents a novel approach in the specification of IP network services, using F-logic knowledge representation framework, aiming to include, in the same specification, the high-level service requirements, the network model and the necessary operations for the deployment of multiple network services.